Anti-Acanthamoeba effect of Camellia sinensis extract (black and green tea) in vitro - Reza Hajihossein; Zahra Eslamirad; Fatemeh Rafiei; Gholamreza Naderi; Morteza Assadi (Institue of Medicinal Plants, ACECR, 2020)
Background: Acanthamoeba is a resistant protozoan that causes severe diseases, such as GAE and CAK. Because many medications are ineffective on the parasite, the quest to find alternative drugs is in progress. Objective: This research was aim ed to assess the performance of the black and green tea extracts on Acanthamoeba. Methods: The clinical isolate of Acanthamoeba was cultured on non-nutrient agar plates. The black and green tea extracts were prepared via maceration, dried by rotary evaporation, and stored at 4 °C. The main component of the extracts (caffeine) was recognized using GC-MS analysis. The effects of three concentrations of black and green tea extracts were evaluated on the parasite and compared with the control and current drug. Results: Black and green tea extracts have lethal effects on Acanthamoeba cysts and the performance was more than that shown by the control and the current anti-keratitis drug. Moreover, the effectiveness of the tea extracts was tim e- and dose-dependent (P < 0.0001). There was no significant differences between the performance of black and green tea (P > 0.05). Conclusion: Black  and green tea extracts demonstrated the potential to inhibit the Acanthamoeba parasite, but the use of tea extract in clinical applications requires further study.